2017
DOI: 10.1016/j.aenj.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The utilisation of one district hospital emergency department by people with Parkinson’s disease

Abstract: We identified in this study that people with PD have a high rate of falls, longer length of stay, high admission rate and represent frequently to the ED. Improved detection, management and a multidisciplinary approach for people with PD along with strict medication regime adherence is likely to improve safety, quality of life, reduce symptom aggravation and ongoing risk of falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The full text articles of 65 studies were then assessed for eligibility, and of these 56 articles were excluded with reasons. Twenty-three [11,16,17,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] of the 56 excluded articles reported reasons for admission among people with PD but did not report exact number of people admitted for the reasons they reported so were excluded. (supplementary material: table 2) Finally, data were captured from a total of nine articles: [14,18,19,[42][43][44][45][46][47].…”
Section: Selection Processesmentioning
confidence: 99%
“…The full text articles of 65 studies were then assessed for eligibility, and of these 56 articles were excluded with reasons. Twenty-three [11,16,17,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] of the 56 excluded articles reported reasons for admission among people with PD but did not report exact number of people admitted for the reasons they reported so were excluded. (supplementary material: table 2) Finally, data were captured from a total of nine articles: [14,18,19,[42][43][44][45][46][47].…”
Section: Selection Processesmentioning
confidence: 99%
“…The practice changes that occurred in response to this project became core business and were incorporated into a clinical guideline for the care and management of patients with PD at presentation and admission to hospital, with the aim of maintaining meaningful long-term sustained change with improved outcomes (Aminoff et al, 2011;Gerlach et al, 2011;Harris & Fry, 2017). These results are promising and reflect the recommendations and conclusions of other research relating to the care and management of patients admitted to hospital with PD (Aminoff et al, 2011;Chenoweth, Sheriff, McAnally, & Tait, 2013;Chou et al, 2011;Cohen & Smetzer, 2015;Donizak & McCabe, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Australian study by Harris and Fry (2017) suggested education and orientation programs should be more specific to PD and identified a need for evidence-based clinical guidelines to support earlier detection and management of PD in the inpatient setting. Greater collaboration among the healthcare team (including pharmacists) was also needed to improve medication administration practices and avoid potential adverse events (Harris & Fry, 2017). It is important to identify a person with PD at presentation/admission to hospital so staff can be alerted to that person's particular needs (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with PD need continuous specialized outpatient care, which can be supplemented by more intensive inpatient treatment (such as PD multimodal complex treatment (PD-MCT), PD day clinic, telemedicine) if necessary [ 4 , 5 , 6 ]. Frequently, PD patients also must consult emergency care at local hospitals [ 7 , 8 ]. Reasons for hospital admission are PD-related symptoms [ 9 ] as well as infections, gastrointestinal disorders, falls, neuropsychiatric, and other health problems.…”
Section: Introductionmentioning
confidence: 99%